4+5x-3+7+3(x-1)=

Simple and best practice solution for 4+5x-3+7+3(x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+5x-3+7+3(x-1)= equation:


Simplifying
4 + 5x + -3 + 7 + 3(x + -1) = 0

Reorder the terms:
4 + 5x + -3 + 7 + 3(-1 + x) = 0
4 + 5x + -3 + 7 + (-1 * 3 + x * 3) = 0
4 + 5x + -3 + 7 + (-3 + 3x) = 0

Reorder the terms:
4 + -3 + 7 + -3 + 5x + 3x = 0

Combine like terms: 4 + -3 = 1
1 + 7 + -3 + 5x + 3x = 0

Combine like terms: 1 + 7 = 8
8 + -3 + 5x + 3x = 0

Combine like terms: 8 + -3 = 5
5 + 5x + 3x = 0

Combine like terms: 5x + 3x = 8x
5 + 8x = 0

Solving
5 + 8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 8x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 8x = 0 + -5
8x = 0 + -5

Combine like terms: 0 + -5 = -5
8x = -5

Divide each side by '8'.
x = -0.625

Simplifying
x = -0.625

See similar equations:

| 3[3a+2]=0 | | 7+3x=-6x+43 | | Ln(x)=-1.386 | | -6(u+1)=-8u-4 | | (3-8i)-(7-4i)=0 | | 7q+2q-p-5q= | | 60p^2+44p-56=0 | | 2(x+3)-(x-5)=x-5-3(x+2)+4x | | -x+4=7x+52 | | x=2.5y-13 | | 3t^2+17+24=0t | | 3(2x-6)=2(3x+9) | | 7x+6-5(-2x-1)=5(x-1) | | 4z=4.25+3.5 | | [(x*5)-12]*4=32 | | 3t^2+17+24=0 | | 2y+3.5-2=10 | | 9x-1=5x+23 | | 25x^2-4=7x(5x-2) | | x^4-2ax^3+1=0 | | 8x+16=11x+25 | | 11x+54=7x+50 | | 24x+12= | | Sec^2x-3secx-2=0 | | 2x^2+7x=14 | | 5x+40=3x+26 | | .2852(X+Y)+(X+Y)=200000 | | 8x+4y-x-7y= | | 5(x-1)+3(x+2)=x+7 | | 6x+30=186 | | 5(x-1)-3(x+1)=4(x-2) | | 2+2x=-22-4x |

Equations solver categories